Effect of Lawyer-Submitted Reports on Signals of Disproportional Reporting in the Food and Drug Administration’s Adverse Event Reporting System - Rogers, James R.; Sarpatwari, Ameet; Desai, Rishi J.; Bohn, Justin M.; Khan, Nazleen F.; Kesselheim, Aaron S.; Fischer, Michael A.; Gagne, Joshua J.; Connolly, John G. (Drug safety, 2019)
Introduction Lawyer-submitted reports may have unintended consequences on safety signal detection in spontaneous adverse event reporting systems. Objective Our objective was to assess the impact of lawyer-submitted reports primarily for one adverse event (AE) on the ability to detect a signal of disproportional reporting for another AE for the same drug in the US FDA Adverse Event Reporting System (FAERS). Methods FAERS reports from January 2004 to September 2015 were used to estimate yearly cumulative proportional reporting ratios (PRRs) for three known drug–AE pairs—isotretinoin–birth defects, atorvastatin–rhabdomyolysis, and rosuvastatin–rhabdomyolysis—with and without lawyer-submitted reports. Isotretinoin and atorvastatin have been the subject of high-profile tort litigation regarding other AEs. A lower bound of the 95% confidence interval (CI) of one or more based on three or more reports defined a signal. Results Cumulative PRRs met signaling criteria in all analyses. For isotretinoin, lawyer-submitted reports increased PRRs for birth defects before 2008, with the largest increase in 2006 (2.9 [95% CI 2.4–3.5] to 3.3 [95% CI 2.8–3.9]); lawyer-submitted reports decreased PRRs for birth defects after 2011, with the largest decrease in 2013 (2.2 [95% CI 2.0–2.5] to 1.9 [95% CI 1.7–2.1]). For atorvastatin, lawyer-submitted reports reduced PRRs for rhabdomyolysis after 2013, with the largest decrease in 2015 (18.0 [95% CI 17.1–19.1] to 15.4 [95% CI 14.5–16.2]). Lawyer-submitted reports had little impact on PRRs for rosuvastatin and rhabdomyolysis. Conclusions Inclusion of lawyer-submitted reports in FAERS did not meaningfully distort known safety signals for two drugs subject to high-profile tort litigation for other AEs.